Nursing students' perception of clinical learning experiences as provided by the nursing staff in the wards - N. R. C. TIakula; L. R. Uys (AOSIS, 1993)
A descriptive survey was carried out, using convenience and systematic sampling in order to better understand the manner in which student nurses perceive their clinical experience in the hospital. Data were collected from 80 subjects in 4 nursing colleges using a critical incident technique. Positive and negative experiences are described,